2021
DOI: 10.1016/j.jtocrr.2021.100184
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab Plus Amrubicin in Patients With Relapsed SCLC: Multi-Institutional, Single-Arm Phase 2 Study

Abstract: Introduction In patients with relapsed SCLC, amrubicin (AMR) is the current standard treatment in Japan. Nevertheless, its efficacy is not satisfactory and prognosis is poor. Preclinical study suggested that anthracycline agent might induce immunogenic cell death and work synergistically with immune checkpoint inhibitors. Methods Patients with relapsed SCLC who relapsed after completion of platinum-containing regimen were registered. Patients were treated with pembroliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Results of a single-arm phase II trial of pembrolizumab, an ICI, in combination with amrubicin in patients with relapsed SCLC were recently reported [ 39 ]. Patients had not received any prior ICIs, but the response rate was 52.0%, the median PFS was 4.0 months, and the median OS was 10.6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Results of a single-arm phase II trial of pembrolizumab, an ICI, in combination with amrubicin in patients with relapsed SCLC were recently reported [ 39 ]. Patients had not received any prior ICIs, but the response rate was 52.0%, the median PFS was 4.0 months, and the median OS was 10.6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Short progression-free survival of 1.4 to 1.9 months has been reported [ 12 , 13 , 14 ]. By contrast, a progression-free survival of 4.0 months was reported in a phase II trial where pembrolizumab was used in addition to amrubicin as a second-line treatment for ES-SCLC [ 15 ]. Anthracyclines such as amrubicin promote the mobilization and recruitment of T-cell antigen-presenting cells to the tumor sites, apart from stimulating immunogenic cell death and interferon secretion [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy using immune checkpoint inhibitors (ICIs), such as programmed cell death 1 (PD‐1), programmed death‐ligand 1 (PD‐L1), and cytotoxic T‐lymphocyte‐associated protein 4, either as single agents or combined with cytotoxic chemotherapy, has revolutionized the treatment of several solid tumors, including SCLC. 18 A recent study has shown that the addition of an anti‐PD‐1 antibody, pembrolizumab, to AMR for relapsed SCLC could afford a remarkable ORR of 52% and PFS rate of 14.4% at one year, 19 indicating the promising effect of AMR when combined with ICIs. For some patients with LD‐SCLC who would benefit from ICIs, a combination with AP may be an optimal strategy in the future.…”
Section: Discussionmentioning
confidence: 99%